Consciência fonológica de crianças pré-escolares: relações com parentalidade, indicadores comportamentais e funcionamento executivo - Burini, Bianca Meireles (2023)
From a developmental perspective, child and environmental characteristics are considered to play an important role in the acquisition of language skills, such as phonological awareness. Executive functioning, as an aspect of child cognitive development, occurs gradually, sharing skills with language, which gives the child an important tool for control and regulation. As a source of influence from the environment is the family context, more specifically, the quality of parenting. This research aimed to investigate the relationships between phonological awareness, quality of parenting, and behavioral and cognitive indicators in preschool children. A descriptive, correlational, quantitative, cross-sectional study was conducted with the participation of 20 children of both genders, 5 and 6 years old, and their parents. The instruments were used: Parenting and Family Adjustment Scale (PAFAS), Inventory of Infant Executive Functioning (IFEI), Abilities and Difficulties Questionnaire (SDQ), answered by the parents; and Proof of phonological awareness by oral production (PCFO), answered by the children. Descriptive and inferential analysis was performed, with Spearman's correlation coefficient. No significant relationships were found between executive functioning and phonological awareness. The latter was associated with behavioral indicators (SDQ) and parenting (PAFAS). A negative correlation was found, suggesting that the greater the difficulty in parents' emotional adjustment, the lower the phonemic segmentation score. There was also a positive correlation between behavior problems (emotional symptoms and total problems) and executive functioning (working memory and inhibitory control). The parents' emotional adjustment and the parent-child relationship were associated with behavioral and executive indicators. We conclude in favor of the importance of contextual variables in the development of behavioral, cognitive, and linguistic variables of preschool children in order to support studies focusing on positive parenting skills intervention with parents.